2015
DOI: 10.4088/jcp.14r09145
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Brief Versus Ultrabrief Right Unilateral Electroconvulsive Therapy for Depression

Abstract: BP compared with UBP RUL ECT was slightly more efficacious in treating depression and required fewer treatment sessions, but led to greater cognitive side effects. The decision of whether to use BP or UBP RUL ECT should be made on an individual patient basis and should be based on a careful weighing of the relative priorities of efficacy versus minimization of cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(115 citation statements)
references
References 0 publications
3
102
1
1
Order By: Relevance
“…A lower proportion of the patients responded to the treatment (54% vs 66.7%). These findings align with those of the meta-analysis, 1 in which patients treated with UBP ECT received a significantly higher number of treatment sessions (9.6 vs 8.7) than patients treated with BP ECT.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…A lower proportion of the patients responded to the treatment (54% vs 66.7%). These findings align with those of the meta-analysis, 1 in which patients treated with UBP ECT received a significantly higher number of treatment sessions (9.6 vs 8.7) than patients treated with BP ECT.…”
supporting
confidence: 88%
“…he endeavor of Tor and colleagues 1 confirms the buzz that has been around for some time. Ultrabrief pulse (UBP) right unilateral (RUL) electroconvulsive therapy (ECT) is an attractive ECT technique, since it has a strong reputation of being cognitively safe.…”
mentioning
confidence: 75%
“…In terms of harms/benefits ratio, high-dose unilateral ECT was noninferior to bitemporal ECT but showed a better cognitive profile, especially for preserving retrograde personal memories and fewer subjective cognitive side effects. While there is much interest in other modifications to maintain effectiveness but reduce side effects (e.g., ultrabrief pulse-width ECT), these require further refinement and characterization for optimization (36,37). Our findings justify considering high-dose unilateral ECT as the preferred ECT option for treating depression and may help improve acceptability and availability of this effective treatment.…”
Section: Discussionmentioning
confidence: 80%
“…26,27 There have been recent claims for marked cognitive benefit from RUL ultra-brief-pulse ECT compared with both bilateral ultra-brief-pulse ECT and all types of brief-pulse ECT without sacrificing efficacy; 19,28 however, a recent meta-analysis of six studies, although confirming the cognitive advantage, found that it came at the price of lower efficacy than for bilateral brief-pulse ECT. 29 The role of glutamate in depression and the effects of electroconvulsive therapy…”
Section: Clinical Use Of Electroconvulsive Therapymentioning
confidence: 99%